Eksistensi Penafsiran Al-Qur’an Perspektif Muhammad ‘Ajaj Al-Khatib dan Pengaplikasiannya - Anam, Masrul (Proceedings of International Conference on Muslim Society and Thought, 2024)
An interpretation of the Qur’an will be continue to development, because each interpreter has a different understanding and intelligence needs to be standardization will be continues to exist. the criteria identify for correct interpretation. Interesting from Muhammad Ajaj al-Khatib is a hadith expert but is able to formulate the existence of an interpretation. This research found that there are six criteria to existence of interpretation,